Pharmacotherapeutic follow-up of patients with Systemic Lupus Erythematus in the city of Piripiri-PI (Research, Society and Development, 2021)
The present study aimed to carry out the pharmacotherapeutic follow-up of patients with SLE in the municipality of Piripiri-PI. The study is a quantitative, descriptive, longitudinal, observational and interventionist field research, using the direct observation technique in patients with SLE, using the Dáder Pharmacotherapeutic Monitoring method. To identify the degree of adherence of this group of patients to medication, the Morisky, Green and Levine test was adopted. Based on the review of the literature, it was found that this is the first quantitative field research study developed in the interior of the state of Piauí to assess adherence to drug therapy in patients with Systemic Lupus Erythematosus. The survey included ten participants, all of whom lived in Piripiri - Piauí, 80% women and 20% men. In total, 23 PRMs were identified, with an average of 2 to 3 for each patient. 20% of patients had low adherence to treatment, 60% with medium adherence and 20% with high adherence. 87.5% of moderate drug interactions, 6.25% mild and 6.25% severe were identified. It is concluded that adherence to drug therapy is a complex and multifactorial problem and that pharmacotherapeutic follow-up is a good alternative to assess adherence and ADRs associated with treatment.